Varying Relationship Between Vascular Plant Leaf Area and Leaf Biomass Along an Elevational Gradient on the Eastern Qinghai-Tibet Plateau - Yang, Ketong; Chen, Guopeng; Xian, Junren; Chen, Weiwei (Frontiers in Plant Science, 2022)
Leaf area (LA) and mass (LM) are key traits for plant metabolic performance. The scaling relationship hypothesis posits that LM and LA exist an intimate relationship, i.e. increases in LA may not keep pace with increases in LM. Specific leaf area (SLA) might increase gradually with increases in LM, which implies that leaf water content (LWC) may disproportionately increase with increases in leaf dry weight (LDW). However, experimental tests of the scaling hypothesis along large elevational gradient natural communities are lacking. To explore the scaling relationship for plant leaf traits (leaf fresh weight (LFW), LDW, LA), we measured about 1800 leaves of 268 woody plant species at 26 altitudes, which ranged from 1050 m to 3500 m located in the eastern Qinghai-Tibet Plateau. We analyzed the relationships between LDW vs. LFW, LA vs. LFW, and LA vs. LDW. We found that, LFW and LDW increased significantly (p < 0.05) with elevation, LA showed a unimodal change (p < 0.05), and other traits had no significant relationship with elevation. The scaling exponents and normalization constants of LDW vs. LFW, LA vs. LFW and LA vs. LDW did not significantly change with altitude, but their extreme-values occurred around 2500 m. All paired traits had positive linear relationships (p < 0.001) between scaling exponents and normalization constants. This result provides a new model for research on allometric theory along large elevational gradients, which could be applied to study the scaling relationships in complex mountain ecosystems and helpful to reveal life-history strategies along elevational gradients.